Kesejahteraan Psikologis dan Kualitas Hidup Pasien Kanker Serviks dengan Kemoterapi - Aniarti, Reni Purwo (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Cervical cancer is a life-threatening gynecological problem in women worldwide. Chemotherapy is one of the treatment options for cervical cancer patients. The side effects of chemotherapy can cause psychological discomfort which has an impact on quality of life. The purpose of the study was to analyze the relationship between psychological well-being and quality of life of cervical cancer patients with chemotherapy. The cross-sectional study approach method was conducted on 89 cervical cancer patients with chemotherapy. Univariate analysis was used to describe the research variables presented in frequency and percentage tables. The chi square test was used to correlate the variables of psychological well-being and quality of life. Psychological well-being was assessed with Ryff's Psychological Well-Being Scale (RPWB) questionnaire with 28 questions. The quality of life of research respondents was assessed with The EORTC Core Quality of Life Questionnaire (QLQ-C30) questionnaire with 30 questions. The results showed that 41 respondents (75.55%) had good psychological well-being and good quality of life while 16 respondents (47.06%) had poor psychological well-being and poor quality of life. The results of the chi square test obtained a p-value of 0.036 which means p < α (α = 0.05). These results indicate that psychological well-being has a significant relationship with quality of life in cervical cancer patients with chemotherapy. The conclusion shows that cancer has a negative impact on the psychological well-being and quality of life of cancer patients. The psychological well-being status and quality of life of cervical cancer patients need to be assessed to reduce side effects during chemotherapy.